2021
DOI: 10.1177/01939459211043937
|View full text |Cite
|
Sign up to set email alerts
|

Loneliness and Depressive Symptoms among Pregnant Black Women during the COVID-19 Pandemic

Abstract: We explored the associations among perceived stress, depressive symptoms, loneliness, and social support during the COVID-19 pandemic; and differences in perceived stress, depressive symptoms, and social support prior to the pandemic and during the pandemic among pregnant Black women. A sample of 33 pregnant Black women who participated in the Biosocial Impact on Black Births (BIBB) and were still pregnant in May–June 2020 were invited to complete an online survey about their experiences during the pandemic. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 29 publications
(52 reference statements)
0
13
0
Order By: Relevance
“…A total of 45 references were selected for a total of 59,329 pregnant women (Table 2). Table 2 shows the summary of the references and associated factors [5]- [49].…”
Section: Resultsmentioning
confidence: 99%
“…A total of 45 references were selected for a total of 59,329 pregnant women (Table 2). Table 2 shows the summary of the references and associated factors [5]- [49].…”
Section: Resultsmentioning
confidence: 99%
“…Maternal loneliness during pregnancy and the postpartum period is associated with several health issues for the mother and her child. Various studies showed a positive correlation between loneliness and depression during pregnancy across countries [5][6][7][8][9][10]. In addition, maternal loneliness is associated with life dissatisfaction and pair-relationship dissatisfaction [9].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Perzow et al in [5] used self-report questionnaires to discern symptoms of depression and anxiety, loneliness, and COVID-19-related adverse health outcomes. In another study, Giurgescu et al [6] used online surveys to investigate the association between loneliness, depression, perceived stress, and social support during the COVID-19 pandemic in pregnant Black women.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations